Confidentiality of 2D Code using Infrared with Cell-level Error Correction - Teraura, Nobuyuki; Sakurai, Kouichi (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
Optical information media printed on paper use printing materials to absorb visible light. There is a 2D code, which may be encrypted but also can possibly be copied. Hence, we envisage an information medium that cannot possibly be copied and thereby offers high security. At the surface, the normal 2D code is printed. The inner layers consist of 2D codes printed using a variety of materials, which absorb certain distinct wavelengths, to form a multilayered 2D code. Information can be distributed among the 2D codes forming the inner layers of the multiplex. Additionally, error correction at cell level can be introduced
Keywords: 2D code; confidenciality; error correction; multilayer; IJIMAI